Recent Progress in Commercial and Novel Catalysts for Catalytic Dehydrogenation of Light Alkanes. Issue 6 (5th December 2019) - Wang, Guowei; Zhu, Xiaolin; Li, Chunyi
Abstract: Catalytic dehydrogenation of light alkanes can effectively produce olefins and hydrogen. Even though Pt and CrOx ‐based catalysts are widely applied in industry, research to improve the activity and stability of these catalysts continued. This review summarizes important achievements obtained in recent years, focusing on the development of supports, promoters and preparation methods of Pt and CrOx ‐based catalysts, which mainly aimed to improve the dispersion of the active species and to enhance coke resistance. Furthermore, the high cost of Pt‐based catalysts and environmental problems encountered with CrOx ‐based catalysts have spurred the development of alternative catalysts. The dehydrogenation performances and characteristics of promising alternative VOx ‐, modified Ni‐ and Sn‐based catalysts are also reviewed. Comparison with the catalytic reforming process of naphtha further probes the necessity of catalyst acidity in these two different processes. The choice of the dehydrogenation reactor is discussed, and future perspectives and research directions are indicated. Abstract : Even though Pt and CrOx dehydrogenation catalysts are widely applied in industry, research to improve the activity and stability of these catalysts continued. This review summarizes important achievements obtained in recent years aimed to improve the dispersion of active species and to enhance coke resistance. Furthermore, the high cost of Pt catalyst and environmental problems encountered with CrOx catalyst have spurred the development of alternative catalysts. Future perspectives and research directions of dehydrogenation are also indicated.